The Effect of Electronic Apparatus on Developing Balance in National Center for Gifted in Boxing and Basketball - Abdul Jaleel Jebar Naser; Ali Ahmed Hadi (College of Physical Education and Sport Sciences, 2021)
The problem of the research lies in special motor abilities training programs like the balance that positively affect coordination between the nervous system and muscles. These training programs did not get enough attention from athletes especially young athletes; their training was restricted to physical abilities like strength, speed, and endurance instead. The research aimed at designing an apparatus for developing athletes' balance in national centers for gifted/ ministry of youth and sport so as to provide a measurement for coached in this field. The results showed that the designed apparatus have a positive effect on developing the subjects' balance in boxing and basketball athletes.